2012
DOI: 10.1016/j.biopsych.2012.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Defensive Mobilization in Specific Phobia: Fear Specificity, Negative Affectivity, and Diagnostic Prominence

Abstract: Background Understanding of exaggerated responsivity in specific phobia—its physiology and neural mediators—has advanced considerably. However, despite strong phenotypic evidence that prominence of specific phobia relative to co-occurring conditions (i.e., principal versus non-principal disorder) is associated with dramatic differences in subjective distress, there is yet no consideration of such comorbidity issues on objective defensive reactivity. Methods A community sample of specific phobia (N=74 princip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(27 citation statements)
references
References 67 publications
(75 reference statements)
2
24
1
Order By: Relevance
“…Given that prior reviews of neurophysiological data suggest there may be some distinctions between (a) phobic and fear disorders, (b) non-phobic anxiety disorders and negative affect, and (c) depressive disorders (see Vaidyanathan et al, 2012), larger studies that can separate these diagnostic categories will be important for informing structural models of internalizing psychopathology (e.g., Watson and Clarke, 2006; Lahey et al, 2008; Seeley et al, 2011), as well as current initiatives, such as the RDoC, which aim to redefine the classification of emotional disorders along neurobiological lines (e.g., Insel and Cuthbert, 2009; Vaidyanathan et al, 2009; Craske, 2012). In contrast to studies of anxious adults (McTeague et al, 2012) but similar to studies with anxious children (Waters et al, 2014b), the present study did not find significant differences in the number of diagnoses or self-report symptom severity between the fear and distress disorder groups. These differences could reflect on developmental differences in the capacity to report on ones’ own problems as well as the actual severity and impairment associated with emotional disorders that increases with advancing age.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…Given that prior reviews of neurophysiological data suggest there may be some distinctions between (a) phobic and fear disorders, (b) non-phobic anxiety disorders and negative affect, and (c) depressive disorders (see Vaidyanathan et al, 2012), larger studies that can separate these diagnostic categories will be important for informing structural models of internalizing psychopathology (e.g., Watson and Clarke, 2006; Lahey et al, 2008; Seeley et al, 2011), as well as current initiatives, such as the RDoC, which aim to redefine the classification of emotional disorders along neurobiological lines (e.g., Insel and Cuthbert, 2009; Vaidyanathan et al, 2009; Craske, 2012). In contrast to studies of anxious adults (McTeague et al, 2012) but similar to studies with anxious children (Waters et al, 2014b), the present study did not find significant differences in the number of diagnoses or self-report symptom severity between the fear and distress disorder groups. These differences could reflect on developmental differences in the capacity to report on ones’ own problems as well as the actual severity and impairment associated with emotional disorders that increases with advancing age.…”
Section: Discussioncontrasting
confidence: 79%
“…Several studies have reported that individuals diagnosed with phobias (e.g., animal phobias; non-generalized social phobia), or with high levels of phobic symptoms or trait fearfulness, demonstrate greater SR magnitudes during aversive picture-viewing or imagery while showing relatively normal baseline SR magnitudes (de Jong et al, 1991; Vrana et al, 1992; Globisch et al, 1999; Cuthbert et al, 2003; Lang et al, 2007; McTeague et al 2009; 2012; Vaidyanathan et al, 2009a). Inconsistent results have been found for panic disorder (Grillon et al, 1994; Vaidyanathan et al, 2009b; McTeague et al, 2011) and generalised social phobia (McTeague et al, 2009), suggesting they may be characterised by more generalised SR activation similar to the broader and more chronic anxiety disorders discussed below.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, 39.1% of children with anxiety disorders had diagnoses of specific phobia, which may be associated with heightened startle responses only in the context of the feared stimulus (McTeague, Lang, Wangelin, Laplante, & Bradley, 2012). …”
mentioning
confidence: 99%
“…Allen, Trinder, & Brennan, 1999), or have high levels of anhedonia (Kaviani et al, 2004). Similarly, in experiments by Lang and colleagues, where subjects are startled in the context of imagined scenes rather than pictures, depressed individuals show a smaller FPS than non-depressed subjects (McTeague et al, 2010; McTeague et al, 2009; McTeague, Lang, Wangelin, Laplante, & Bradley, 2012). Those with a greater number of recurrent episodes also have a smaller FPS than those with just single episodes of depression or those without depression.…”
Section: Understanding Mental Disorders Using Theory and Risky Testsmentioning
confidence: 74%